Electronic Longitudinal Alcohol Study in Communities (ELAStiC) Wales – protocol for platform development - Trefan, Laszlo; Akbari, Ashley; Paranjothy, Shantini; Farewell, Daniel Mark; Gartner, Andrea; Fone, David; Greene, Giles Jeremy; Evans, Anette; Smith, Ann; Adekanmbi, Victor; Kennedy, Jonathan; Lyons, Ronan Anthony; et al. (International Journal of Population Data Science, 2019)
Introduction Excessive alcohol consumption has adverse effects on health and there is a recognised need for thelongitudinal analysis of population data to improve our understanding of the patterns of alcohol use,harms to consumers and those in their immediate environment. The UK has a number of linkable,longitudinal databases that if assembled properly could support valuable research on this topic. Aims and objectives This paper describes the development of a broad set of cross-linked cohorts, e-cohorts, surveys andlinked electronic healthcare records (EHRs) to construct an alcohol-specific analytical platform inthe United Kingdom using datasets on the population of Wales. The objective of this paper is to provide a description of existing key datasets integrated withexisting, routinely collected electronic health data on a secure platform, and relevant derived variablesto enable population-based research on alcohol-related harm in Wales. We illustrate our use of thesedata with some exemplar research questions that are currently under investigation. Methods Record-linkage of routine and observational datasets. Routine data includes hospital admissions,general practice, and cohorts specific to children. Two observational studies were included. Routinesocioeconomic descriptors and mortality data were also linked. Conclusion We described a record-linked, population-based research protocol for alcohol related harm on a secureplatform. As the datasets used here are available in many countries, ELAStiC provides a templatefor setting up similar initiatives in other countries. We have also defined a number of alcohol specificvariables using routinely-collected available data that can be used in other epidemiological studiesinto alcohol related outcomes. With over 10 years of longitudinal data, it will help to understandalcohol-related disease and health trajectories across the lifespan.